2018
DOI: 10.1142/s021798491850104x
|View full text |Cite
|
Sign up to set email alerts
|

Lump solutions with interaction phenomena in the (2+1)-dimensional Ito equation

Abstract: In this paper, we consider the (2+1)-dimensional Ito equation, which was introduced by Ito. By considering the Hirota’s bilinear method, and using the positive quadratic function, we obtain some lump solutions of the Ito equation. In order to ensure rational localization and analyticity of these lump solutions, some sufficient and necessary conditions are provided on the parameters that appeared in the solutions. Furthermore, the interaction solutions between lump solutions and the stripe solitons are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We note that the relations in Equation 7are the same as those in Yang et al (2017), Ma et al (2017), and Zou et al (2018). The Equation (8) indicates four cases…”
Section: Periodic Wave Solutions and Nonelastic Interactional Solutionsmentioning
confidence: 68%
See 2 more Smart Citations
“…We note that the relations in Equation 7are the same as those in Yang et al (2017), Ma et al (2017), and Zou et al (2018). The Equation (8) indicates four cases…”
Section: Periodic Wave Solutions and Nonelastic Interactional Solutionsmentioning
confidence: 68%
“…,, andZou et al (2018). If p ¼ 0 or q ¼ 0, the test function f is similar to that inTang et al (2016),Yang et al (2017), andMa et al (2017).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…where D is a bilinear differential operator as follows [8]: [36], lump and lump-soliton solutions [37], interaction solutions between lump solutions and stripe solitons [38], rogue waves and multi-wave solutions [39], homoclinic breather waves [40]. In this paper, we will study other diverse exact analytical solutions of equation (6).…”
Section: Exact Analytical Solutions Of (2+1)-dimensional Ito Equationmentioning
confidence: 99%
“…Very recently, it has also been shown that there are diverse interaction solutions to Eq. (1.1) [14,28] and even to linear equations [16] and there are abundant lump solutions to other nonlinear equations [13] [10] [11]. The framework of this paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%